2012
DOI: 10.1111/j.1526-4610.2012.02249.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sex and Estrogens on Neuronal Activation in an Animal Model of Migraine

Abstract: These data provide a support for the existence of a sexual dimorphism in NTG-induced neuronal activation, and they prompt a specific model for evaluating and modulating the influence of estrogens upon the cerebral structures implicated in the pathophysiology of migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 48 publications
2
40
0
Order By: Relevance
“…It has previously been reported that systemic GTN administration produces a greater mechanical hyperalgesia in female mice (Pradhan et al, 2014) and a greater increase expression of FOS protein (a marker of neuronal activity) in brain nuclei associated with pain processing of females rats (Greco et al, 2013). Although there is a markedly higher prevalence of migraine in women and a marked reduction in pain severity following depletion of female sex steroids (Brandes, 2006), to our knowledge sex differences in migraine severity induced by GTN infusion in human studies has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that systemic GTN administration produces a greater mechanical hyperalgesia in female mice (Pradhan et al, 2014) and a greater increase expression of FOS protein (a marker of neuronal activity) in brain nuclei associated with pain processing of females rats (Greco et al, 2013). Although there is a markedly higher prevalence of migraine in women and a marked reduction in pain severity following depletion of female sex steroids (Brandes, 2006), to our knowledge sex differences in migraine severity induced by GTN infusion in human studies has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is a need for basic science in translational medicine, as translating findings from animal models to the human condition has been a challenge. In the migraine field, there are a number of “animal models”, however, most use male animals (e.g., (113, 186)), which confounds sex differences in migraine. Another approach to study the influence of hormones is to investigate short term and long term effects of contraceptive use on migraine, as there is compelling evidence that oral contraceptive alter brain function (187, 188) and structure in regions such as the prefrontal cortex, pre- and post-central gyri, parahippocampal and fusiform gyri, and temporal regions (43).…”
Section: Future Directionsmentioning
confidence: 99%
“…It is postulated that estrogen and estrogen receptors in the sensory pathways may alter sensitivity to nociception in these neurons (186). …”
Section: Figurementioning
confidence: 99%
“…However, after puberty, migraine prevalence in women is more than threefold compared with that of men [116,120]. Migraine frequency and intensity have been shown to be influenced by hormonal events such as menstruation, pregnancy and menopause [121][122][123][124][125][126][127][128]. Steroid hormones, estrogen and progesterone, modulators of the menstrual cycle, have thus been considered a triggering factor involved in the onset of many migraine attacks [129].…”
Section: Hormone Receptor Genesmentioning
confidence: 98%